The Relationship between Economic Growth and Economic Development: A Regional Assessment in South Africa - MEYER, Daniel Francois; MASEHLA, T. M.; KOT, Sebastian (Journal of Advanced Research in Law and Economics; Vol 8 No 4(26) (2017): JARLE Volume 8 Issue 4(26) Summer 2017, 2017)
The concepts of economic development and economic growth differ significantly, but are in some instances used as interchangeable notions. It is important for policy formulators and decision makers to understand the relationship between the two. Development strategies should be formulated to achieve sustainable inclusive economic growth and economic development. These two economic concepts influence each other; however, there is limited clarity on the relationship. The aim of the study was to determine the relationship between these in the Vaal Triangle region, South Africa. Economic development is a broad concept and various methods can be used to measure it. For the purpose of this research, an economic development index was developed, which consists of employment, poverty levels and human development index (HDI). This index assists in the measurement of the relationship between economic development and economic growth. A time series econometric model was used to measure the relationship between the two variables. The results indicated that economic development causes economic growth in the long and short run. Therefore, it is important to focus on economic development, through improved HDI, increased employment and poverty alleviation, in order to achieve inclusive economic growth.